Non-linear conversion of HX4 uptake for automatic segmentation of hypoxic volumes and dose prescription. (3rd April 2018) - Ureba, Ana; Lindblom, Emely; Dasu, Alexandru; Uhrdin, Johan; Even, Aniek J. G.; van Elmpt, Wouter; Lambin, Philippe; Wersäll, Peter; Toma-Dasu, Iuliana
Abstract: Background: Tumour hypoxia is associated with increased radioresistance and poor response to radiotherapy. Pre-treatment assessment of tumour oxygenation could therefore give the possibility to tailor the treatment by calculating the required boost dose needed to overcome the increased radioresistance in hypoxic tumours. This study concerned the derivation of a non-linear conversion function between the uptake of the hypoxia-PET tracer 18 F-HX4 and oxygen partial pressure ( pO 2 ). Material and methods: Building on previous experience with FMISO including experimental data on tracer uptake and pO 2, tracer-specific model parameters were derived for converting the normalised HX4-uptake at the optimal imaging time point to pO 2 . The conversion function was implemented in a Python-based computational platform utilising the scripting and the registration modules of the treatment planning system RayStation. Subsequently, the conversion function was applied to determine the pO 2 in eight non-small-cell lung cancer (NSCLC) patients imaged with HX4-PET before the start of radiotherapy. Automatic segmentation of hypoxic target volumes (HTVs) was then performed using thresholds around 10 mmHg. The HTVs were compared to sub-volumes segmented based on a tumour-to-blood ratio (TBR) of 1.4 using the aortic arch as the reference oxygenated region. The boost dose required to achieve 95% local control was then calculated based on the calibrated levels of hypoxia, assuming inter-fraction reoxygenation due to changes in acute hypoxia but no overall improvement of the oxygenation status. Results: Using the developed conversion tool, HTVs could be obtained using pO 2 a threshold of 10 mmHg which were in agreement with the TBR segmentation. The dose levels required to the HTVs to achieve local control were feasible, being around 70–80 Gy in 24 fractions. Conclusions: Non-linear conversion of tracer uptake to pO 2 in NSCLC imaged with HX4-PET allows a quantitative determination of the dose-boost needed to achieve a high probability of local control.